Null-Controllability of a Diffusion Equation with Fractional Integro-Differential Expressions (Analysis in Theory and Applications, 2023)
The article considers the controllability of a diffusion equation with fractional integro-differential expressions. We prove that the resulting equation is null-controllable in arbitrary small time. Our method reduces essentially to the study ofclassical moment problems.